Evaluasi Pelaksanaan Pembelajaran Daring Pendidikan Jasmani pada Masa Pandemi Covid-19 di SMP Negeri Se-Kecamatan Blora - Zainal Mahfudli Sahli; Harry Pramono (Universitas Negeri Semarang, 2022)
Online learning is a learning that uses the Internet network with accessibility, connectivity, flexibility, and capability to display various learning interaction. The learning system lasts without face-to-face offline meeting between the teacher and the learners. At the beginning of 2020 and the outbreak of COVID-19, the government closed the offline learning access and changed into the Internet learning access. This research aims to find out the online learning promotion of physical education during the COVID-19 pandemic in all Public JHS in Blora district. This qualitative research used descriptive approach. The researcher collected the non-numerical data. The data were description and words. The data collecting techniques were observation, interview, and documentation. The subjects included the principals and the physical teachers of all Public JHS in Blora district. From the findings and discussion, the online physical learning process during the COVID-19 pandemic in all Public JHS in Blora were not running excellently. The teachers did not promote the learning planning and learning promotion as expected.